Can simple behavioural interventions increase daily physical activity in Parkinson’s disease? - Opara, Józef; Grzybowska-Ganszczyk, Dominika (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Physical activity (PA) is a modiﬁable factor that may inﬂuence the course of Parkinson’s disease (PD). This study aimed to apply a simple behavioural intervention aimed at encouraging PD suﬀerers to increase their everyday PA and to as-sess which parameters of motor functions will be improved.Methods. The research covered 50 PD patients (28 men and 22 women) aged 40–81 years (65.38 ± 9.23), with a duration of the disease of 2–4 years, in stages 1–3 on the Hoehn and Yahr scale. The patients were randomly divided into two groups: the experimental group with behavioural therapy and the control group without intervention. During 12 weeks, the patients from the experimental group had ﬁve phone conversations. Each conversation lasted 15 min and was an interview about the subjects’ PA in the last month. The outcome was measured by the Timed Up and Go test (TUG), Uniﬁed Parkinson’s Disease Rating Scale (UPDRS) – part III, FIR [Functional Index “Repty” – own modiﬁcation of Functional Independence Measure (FIM)], Functional Ambulation Category (FAC), and International Physical Activity Questionnaire (IPAQ).Results. The results showed that, after 12 weeks and ﬁve phone conversations, in the experimental group spontaneous PA in-creased and motor functions improved.Conclusions. PA improvement depended on age, body mass index, and gender.
Keywords: Parkinson’s disease; physical activity; sedentary lifestyle; walking